Erythropoietin improves the accumulation and therapeutic effects of carboplatin by enhancing tumor vascularization and perfusion - Doleschel, Dennis; Rix, Anne; Arns, Susanne; Palmowski, Karin; Gremse, Felix; Merkle, Ruth; Schwörer, Florian; Klingmüller, Ursula; Jarsch, Michael; Kiessling, Fabian; Lederle, Wiltrud (Theranostics, 2015)
Recombinant human erythropoietin (rhuEpo) is currently under debate for the treatment of chemotherapy-induced anemia due to clinical trials showing adverse effects in Epo-treated patients and the discovery of the erythropoietin-receptor (EpoR) in tumor and endothelial cells. Here, using Epo-Cy5.5 as theranostic near-infrared fluorescent probe we analyzed the effects of rhuEpo as co-medication to carboplatin in non-small-cell-lung-cancer (NSCLC)-xenografts with different tumor cell EpoR-expression (H838 ~8-fold higher than A549). Nude mice bearing subcutaneous A549 and H838 NSCLC-xenografts received either only carboplatin or carboplatin and co-medication of rhuEpo in two different doses. Tumor sizes and relative blood volumes (rBV) were longitudinally measured by 3D-contrast-enhanced ultrasound (3D-US). Tumoral EpoR-levels were determined by combined fluorescence molecular tomography (FMT)/ micro computed tomography (µCT) hybrid imaging. We found that rhuEpo predominantly acted on the tumor endothelium. In both xenografts, rhuEpo co-medication significantly increased vessel densities, diameters and the amount of perfused vessels. Accordingly, rhuEpo induced EpoR-phoshorylation and stimulated proliferation of endothelial cells. However, compared with solely carboplatin-treated tumors, tumor growth was significantly slower in the groups co-medicated with rhuEpo. This is explained by the Epo-mediated vascular remodeling leading to improved drug delivery as obvious by a more than 2-fold higher carboplatin accumulation and significantly enhanced tumor apoptosis. In addition, co-medication of rhuEpo reduced tumor hypoxia and diminished intratumoral EpoR-levels which continuously increased during carboplatin (Cp) -treatment. These findings suggest that co-medication of rhuEpo in well balanced doses can be used to improve the accumulation of anticancer drugs. Doses and indications may be personalized and refined using theranostic EpoR-probes.
Gesehen am 15.06.2020